Seeking security in an insecure world - Caldwell, Dan; Williams, Robert E. (Rowman & Littlefield Publishers, Inc., 2016)
This revised edition of Seeking Security in an Insecure World provides a thorough, accessible introduction to contemporary security studies. All chapters are updated and a wide range of new topics are discussed, including the Syrian civil war, Russia's annexation of Crimea and its intervention in East Ukraine, the global refugee crisis, China's military buildup, the impact of fracking on oil and gas markets, and rapidly evolving cyberwar capabilities.